Pengaruh Perilaku Inovatif dan Motivasi terhadap Produktivitas Kerja pada Pegawai BBPJS Kesehatan di Kantor Cabang Tondano: (The Role of Transformational Leadership, Competence, Readiness to Change in Achieving Performance during a Pandemic) - Vinno Petrus Manoppo; Ripka Fitri Mayangsari; Hennij Lenny Suot (UPT Penerbitan Universitas Jember, 2022)
The purpose of this study is to see the effect of innovative behavior and motivation on work productivity of BPJS Kesehatan employees at the Tondano Branch Office, both partially and simultaneously. This data comes from respondents' answers (questionnaires), as well as the results of the main data research, namely BPJS Kesehatan Tondano Branch Office, using a quantitative method using multiple linear analysis and SPSS 25 assistance. The sample used is 35 employees of BPJS Kesehatan KC Tondano, the sample is drawn using the method probability sampling, while the sampling method used is saturated sampling. The results of this study prove that: (1) Innovative Behavior has a significant effect on the Work Productivity of BPJS Kesehatan Employees at the Tondano Branch Office. (2) Motivation has a significant effect on the Work Productivity of BPJS Kesehatan Employees at the Tondano Branch Office. (3) This study proves that there is a simultaneous or significant effect of innovative behavior and motivation on work productivity of employees at BPJS KC Tondano, so it can be said that innovative behavior and motivation are increasing and applied to employees of BPJS Kesehatan KC Tondano , will be a driver of increasing work productivity.